2019
DOI: 10.1093/jncics/pkz007
|View full text |Cite
|
Sign up to set email alerts
|

Trends in International Incidence of Pediatric Cancers in Children Under 5 Years of Age: 1988–2012

Abstract: Background Pediatric cancer incidence has been steadily increasing over the last several decades with the largest increases reported in infants. Few evaluations have looked at international pediatric cancer incidence trends in the youngest children. The aim of this analysis was to evaluate trends in cancer incidence in children under 5 years of age, overall and by type, using data from Cancer Incidence in 5 Continents (CI5) from 1988 to 2012 (CI5 volumes VII–XI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 28 publications
6
74
0
Order By: Relevance
“…A recent report on trends in international incidence of pediatric cancers among children aged under 5 years reported increasing incidence rates for childhood HB from 1988 to 2012 in all regions except southern Asia (India, Iran) with the strongest increases being seen for countries classified as having high and very high human development index (HDI). 44 Their results indicated that HB was the fastest rising cancer globally for this age group, although no specific reasons for this pattern were presented, reflecting the generally poor understanding of childhood HB aetiology.…”
Section: Discussionmentioning
confidence: 96%
“…A recent report on trends in international incidence of pediatric cancers among children aged under 5 years reported increasing incidence rates for childhood HB from 1988 to 2012 in all regions except southern Asia (India, Iran) with the strongest increases being seen for countries classified as having high and very high human development index (HDI). 44 Their results indicated that HB was the fastest rising cancer globally for this age group, although no specific reasons for this pattern were presented, reflecting the generally poor understanding of childhood HB aetiology.…”
Section: Discussionmentioning
confidence: 96%
“…However, this also contributed to the high proportion of RB and HB in this group of patients. Hubbard et al 9 evaluating 25 years of cancer incidence in children showed that the incidence of NB was increasing, while the incidence of germ cell tumors was declining. The occurrence of tumors also differed among ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1988 and 2012, hepatoblastoma was the fastestrising cancer globally in children <5 years. 5 It is more common in countries with a very high human development index, a statistical marker of relative affluence, where the incidence has changed from 0.8 to 5.6 per million. The overall estimated average annual percent change is 3.43 (CI 2.73-4.13).…”
Section: To the Editormentioning
confidence: 99%
“…The overall estimated average annual percent change is 3.43 (CI 2.73-4.13). 5 There is a popular assumption that overall improvements in neonatal care, leading to better survival of infants born with low birth weight, may be contributing to the several-fold increase in hepatoblastoma incidence in the developed world.…”
Section: To the Editormentioning
confidence: 99%